Physical activity and the prevention, reduction, and treatment of alcohol and other drug use across the lifespan (The PHASE review): A systematic review. (October 2020) - Thompson, T.P.; Horrell, J.; Taylor, A.H.; Wanner, A.; Husk, K.; Wei, Y.; Creanor, S.; Kandiyali, R.; Neale, J.; Sinclair, J.; Nasser, M.; Wallace, G.
Abstract: The aim of this review is to systematically describe and quantify the effects of PA interventions on alcohol and other drug use outcomes, and to identify any apparent effect of PA dose and type, possible mechanisms of effect, and any other aspect of intervention delivery (e.g. key behaviour change processes), within a framework to inform the design and evaluation of future interventions. Systematic searches were designed to identify published and grey literature on the role of PA for reducing the risk of progression to alcohol and other drug use (PREVENTION), supporting individuals to reduce alcohol and other drug use for harm reduction (REDUCTION), and promote abstinence and relapse prevention during and after treatment of alcohol and other drug use (TREATMENT). Searches identified 49, 518 records, with 49, 342 excluded on title and abstract. We screened 176 full text articles from which we included 32 studies in 32 papers with quantitative results of relevance to this review. Meta-analysis of two studies showed a significant effect of PA on prevention of alcohol initiation (risk ratio [RR]: 0.72, 95%CI: 0.61 to 0.85). Meta-analysis of four studies showed no clear evidence for an effect of PA on alcohol consumption (Standardised Mean Difference [SMD]: 0.19, 95%, Confidence Interval −0.57 to 0.18). We were unable to quantitatively examine the effects of PA interventions on other drug use alone, or in combination with alcohol use, for prevention, reduction or treatment. Among the 19 treatment studies with an alcohol and other drug use outcome, there was a trend for promising short-term effect but with limited information about intervention fidelity and exercise dose, there was a moderate to high risk of bias. We identified no studies reporting the cost-effectiveness of interventions. More rigorous and well-designed research is needed. Our novel approach to the review provides a clearer guide to achieve this in future research questions addressed to inform policy and practice for different populations and settings. Highlights: A comprehensive systematic review of physical activity and alcohol and/or substance use. Looks at the prevention, reduction, and treatment of alcohol and/or substance use. Highlights what may be most effective and gaps in knowledge. Considers different elements of physical activity interventions for best practice.